The Citizen's Guide to Climate Success Overcoming Myths that Hinder Progress - Jaccard, Mark (Social Sciences, 2020)
Concerned citizens can drive the energy transition needed to prevent climate change by their personal choices and their identification and support of climate-sincere politicians. Jaccard explains the simplicity and modest cost of decarbonizing electricity and transportation in developed countries and spreading that critical change worldwide.